Plato's Timaeus and the foundations of cosmology in Late Antiquity, the Middle Ages and Renaissance - Leinkauf, Thomas; Steel, Carlos (Leuven Leuven University Press, 2005)
The particular focus of this volume is a study of the influence of Timaeus on the development of Western cosmology in three axial periods of European culture: Late Antiquity, Middle Ages and Renaissance. In each period, the Timaeus was read in a different context and from different perspectives. During the Middle Ages, scholars were mostly interested in reconciling the rational cosmology of the Timaeus with the Christian understanding of creation.In Late Antiquity, the concordance of Plato with Aristotle was considered the most important issue, whereas in early modern times, the confrontation with the new mathematical physics offered possibilities for a fresh assessment of Plato's explanation of the cosmos. The present volume has three sections corresponding to these three periods of interpreting the Timaeus, each section is introduced by a synthesis of the main issues at discussion. This 'epochal' approach gives this volume its particular character.
Keywords: Plato -- 428/427-348/347 BC; Classical Antiquity (8th Century BC-6th Century AD); Middle Ages (500-1400); Renaissance (1400-1600); Philosophy